Kebijakan Strategi Komunikasi Pariwisata Dinas Kebudayaan dan Pariwisata Kota Sabang Melalui Ujung Barat Festival - Muda, Indra; Barus, Rehia K.I; Bukit, Niarita (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Provinsi Sumatera Utara, 2024)
The West End Festival is an annual event initiated through the collaboration of the Aceh and Sabang cultural and tourism offices. The event aims to inform and emphasize to the national and international communities that the city of Sabang is ready to welcome visitors. This research aims to understand the tourism communication strategies of the Sabang cultural and tourism office through the West End Festival event. The research is descriptive with qualitative data, and data collection techniques include in-depth interviews, observation, and literature study. The results of the research indicate that the tourism communication strategy of the Sabang cultural and tourism office through the West End Indonesia Festival is carried out using Tourism Communication Marketing (TCM), highlighting Aceh's cultural attractions accompanied by a Small and Medium Enterprises (UMKM) bazaar supported by the Sabang government and music performances by local musicians born in Sabang. The strategy further involves creating a destination brand with the title